Motivi in teme v najnovejših komedijah Toneta Partljiča in Vinka Möderndorferja - Pezdirc-Bartol, Mateja (Jezik in slovstvo, 2005)
The article is an analysis of ten most recent comedies by Tone Partljič, collected in the books Komedije (Comedies, 1979) and Izbrane komedije I, II, III (Selected comedies I, II, III, 2003), and seven comedies by Vinko Möderndorfer, published in Vaja zbora - tri komedije (Rehersal for Choir - Three comedies, 1998) and Limonada slovenica: štiri komedije (Soap Opera Slovenica: Four comedies, 2003). The results of the analysis show that in their comedies they frequently emply thematic elements of capital in the society and the issue of upstarts, relations between the urban and the rural world, and, to large extent, also political events: elections, party discords, lust for power, and responses to different topical questions of our time. However, rare are the comedies without a social engagement eith a pronounced erotic component, or those merely aiming to entertain. Comical effects most frequently arise from the elements of situational comedy and the domedy of characters, with added numerous linguistic ambiguities, misunderstandings, and puns. As illustrated by its most engaged and successful writers, Slovene comedy critically responds to the current events within the society, is topical and therefore also bound to the time of its creation. In this sense, Möderndorfer is more universal, paying more attention to the linguistic ambiguities and situational entanglements, while Partljič foreground topical political situations, ridiculing the elements of everyday life.
Keywords: Möderndorfer, Vinko; motivi; Partljič, Tone; Slovene literature; slovenska književnost; slovenska komedija; tematika